(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2018)
This study analyses the definition and the concept of restorative justice, and how restorative justice is different from retributive justice. Referring to the principles provided by the United Nations known as the ’Basic Principles on the use of Restorative Justice Programmes in Criminal Matters’, this study analyses how restorative justice protects and balances the rights of offenders and the victims. This study was also conducted to examine the legal position in Malaysia, especially under the Criminal Procedure Code Act 2012 on restorative justice. This study also determines whether the law under the Malaysian Criminal Procedure Code Act is sufficient to protect and to balance the rights of offenders and the victims, as it is in restorative justice. The principles of restorative justice provided by the United Nations can be used as reference and as a benchmark for Malaysia to implement restorative justice in the criminal justice system. Keywords: restorative justice, rights of the accused, rights of victims